Multimodal Electrocorticogram Active Electrode Array Based on Zinc Oxide‐Thin Film Transistors. Issue 2 (20th November 2022) - Zhang, Fan; Zhang, Luxi; Xia, Jie; Zhao, Wanpeng; Dong, Shurong; Ye, Zhi; Pan, Gang; Luo, Jikui; Zhang, Shaomin
Abstract: Active electrocorticogram (ECoG) electrodes can amplify weak electrophysiological signals and improve anti‐interference ability; however, traditional active electrodes are opaque and cannot realize photoelectric collaborative observation. In this study, an active and fully transparent ECoG array based on zinc oxide thin‐film transistors (ZnO TFTs) is developed as a local neural signal amplifier for electrophysiological monitoring. The transparency of the proposed ECoG array is up to 85%, which is superior to that of the previously reported active electrode arrays. Various electrical characterizations have demonstrated its ability to record electrophysiological signals with a higher signal‐to‐noise ratio of 19.9 dB compared to the Au grid (13.2 dB). The high transparency of the ZnO‐TFT electrode array allows the concurrent collection of high‐quality electrophysiological signals (32.2 dB) under direct optical stimulation of the optogenetic mice brain. The ECoG array can also work under 7‐Tesla magnetic resonance imaging to record local brain signals without affecting brain tissue imaging. As the most transparent active ECoG array to date, it provides a powerful multimodal tool for brain observation, including recording brain activity under synchronized optical modulation and 7‐Tesla magnetic resonance imaging. Abstract : An electrocorticogram active transparent electrode array that uses zinc oxide thin‐film transistors as a local neural signal amplifier is proposed. As the most transparent active ECoG array to date, it allows monitoring of electrophysiological signals with synchronized optical modulation, 7‐Tesla magnetic resonance imaging, and optical imaging, providing a powerful multimodal tool for brain research.